Attractiveness of recreational forests: an overview on selected research - Idris, Nur Hafizah; Aziz, Azlizam; Mariapan, Manohar; Jamaludin, Mazlina (Asian Institute of Advance Research and Studies, 2013)
The purpose of this study is to discuss the challenges and potentials for transforming recreational forests in Peninsular Malaysia as viable ecotourism destination. The selected research and articles of recreational forest were accumulated in determining the lack and weakness of the forest. In fact, recreational forests have the potential to be developed and marketed as ecotourism destinations since our forests are endowed with diverse flora and fauna, as well as other natural destinations. Some of the recreational forests really famous but some are seems to have no visitors. Several challenges are also noted in this paper which needs to be addressed before the potential can be translated into a real tourism product. This include the lack of competence pool of personnel to carryout tasks necessary to receive visitors, lack of maintenance of current facilities, lack of structured programming of ecotourism activities and the non-existence of a concerted efforts in properly developed the recreational forests as a ecotourism destinations. Once such issues are addressed, recreational forests can help to diversify and adding a unique dimension into our ecotourism and outdoor recreation sector.